2010
DOI: 10.3945/jn.109.110981
|View full text |Cite
|
Sign up to set email alerts
|

The Soybean Isoflavonoid Equol Blocks Ritonavir-Induced Endothelial Dysfunction in Porcine Pulmonary Arteries and Human Pulmonary Artery Endothelial Cells

Abstract: HIV protease inhibitor (PI) ritonavir (RTV) may cause vascular injury through oxidative stress. Our purpose in this study was to determine whether equol, a soy isoflavone, could prevent RTV-induced endothelial dysfunction in porcine pulmonary arteries and in human pulmonary artery endothelial cells (HPAEC). Fresh porcine pulmonary artery rings were treated with 15 micromol/L of RTV and/or equol in concentrations of 0.1, 1, and 10 micromol/L for 24 h. A control was set with no amount of equol or RTV administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 36 publications
1
28
0
1
Order By: Relevance
“…Ouellet et al [5] reported that RTV reduces estrogen levels in the blood by 40% in healthy female volunteers. In addition, Cheng et al [3] showed that the soybean isoflavonoid equol blocks RTV-induced endothelial dysfunction in porcine pulmonary arteries and human pulmonary artery endothelial cells. These studies suggested that RTV may lead Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ouellet et al [5] reported that RTV reduces estrogen levels in the blood by 40% in healthy female volunteers. In addition, Cheng et al [3] showed that the soybean isoflavonoid equol blocks RTV-induced endothelial dysfunction in porcine pulmonary arteries and human pulmonary artery endothelial cells. These studies suggested that RTV may lead Fig.…”
Section: Discussionmentioning
confidence: 98%
“…However, more and more evidences have shown that RTV induces body fat changes and metabolic abnormalities, and many patients have developed premature atherosclerosis [1][2][3]. These side effects induced by PI have prevented the broad application of PIs.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…PAH has been shown to be caused by the anti-HIV protease drug ritonavir [117][118][119]. It apparently does this, at least in part, via increased oxidative stress, because multiple chainbreaking antioxidants greatly lower this effect of the drug [117][118][119]. Ritonavir has been shown to increase superoxide production [117,120] in mitochondria [121], showing that both superoxide and mitochondrial dysfunction have roles here.…”
Section: Principlementioning
confidence: 99%
“…PAH has been shown to be caused by the anti-HIV protease drug ritonavir [117][118][119]. It apparently does this, at least in part, via increased oxidative stress, because multiple chainbreaking antioxidants greatly lower this effect of the drug [117][118][119].…”
Section: Principlementioning
confidence: 99%